2023
DOI: 10.1096/fj.202300742r
|View full text |Cite
|
Sign up to set email alerts
|

Placental DNA methylation analysis of selective fetal growth restriction in monochorionic twins reveals aberrant methylated CYP11A1 gene for fetal growth restriction

Dayuan Shi,
Xinyao Zhou,
Luyao Cai
et al.

Abstract: Fetal growth restriction (FGR) is associated with increased susceptibility to perinatal morbidity and mortality. Evidence suggests that epigenetic changes play critical roles in the regulation of fetal growth. We sought to present a comprehensive analysis of the associations between placental DNA methylation and selective fetal growth restriction (sFGR), which is a severe complication of monochorionic twin pregnancies, characterized by one fetus experiencing restricted growth. Genome‐wide methylation analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Despite the differences in cellular composition between non-malarial FGR and PM-FGR, the differentially methylated CpGs were distinct from those associated with specific cell types. In contrast, a study that conducted the same deconvolution analysis on placentas from monochorionic twins complicated by selective FGR found decreased proportions of stromal cells with FGR compared the normally grown twin (41). This suggests a distinct placental response to FGR in twins compared with singletons.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite the differences in cellular composition between non-malarial FGR and PM-FGR, the differentially methylated CpGs were distinct from those associated with specific cell types. In contrast, a study that conducted the same deconvolution analysis on placentas from monochorionic twins complicated by selective FGR found decreased proportions of stromal cells with FGR compared the normally grown twin (41). This suggests a distinct placental response to FGR in twins compared with singletons.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies investigating placental epigenetic changes occurring with FGR have identified various differentially methylated CpG sites and related genes involved with fatty acid oxidation, transcriptional regulation, immune responses, cell adhesion, metabolism, cell growth (32,4144). Our results did not have any clear overlap between the most of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several of the genes and epigenetic loci that we identified as differentially methylated in association with increasing placental PFAS concentrations have been associated with other endocrine disrupting chemicals and with cardiometabolic outcomes. For instance, multiple CpGs within XKR6 , among other CpGs and genes, were found to have lower DNA methylation levels among placenta of newborns with selective fetal growth restriction [26]. Higher levels of maternal urinary bisphenol A (BPA) concentrations were associated with lower DNA methylation of one CpG in XKR6 [27].…”
Section: Discussionmentioning
confidence: 99%